Film Biopik Sebagai Produksi Citra Dan Seni Yang Politis: Film Soekarno (2013) Dan Terkait Dugaan Desoekarnoisasi - Febriyanti Pratiwi (Universitas Budi Luhur, 2026)
This paper elaborates on the production of Ir. Soekarno's image in the film Soekarno (2013) by Hanung Bramantyo. The figure of Soekarno in the context of Indonesian cinema always presents its polemic about how the proclaimer is presented. Allegations of desokarnoization were rapidly directed at the film Soekarno (2013). This research aims to examine the capacity of the film apparatus in producing Soekarno through the actor's body, visuals, and historical selection. The film Soekarno (2013) cannot be separated from the stereotype of biopic films full of political decisions about how historical figures are presented in 'new versions'. The Aura of The Original Soekarno cannot appear completely in a film format with limited duration and visuals. The allegation of Desoekarnoization is weak to be aimed at the film Soekarno (2013) which was produced selectively and specifically in choosing the story of Soekarno's life. Keywords : Biopic film, Soekarno, Image production, Desoekarnoization.